DETERMINANTS OF BUY NOW PAY LATER USAGE DECISIONS MEDIATED BY BEHAVIORAL CONTROL AMONG GENERATION Z IN BALI - Ni Putu Eka Setiasih; Ni Putu Sri Harta Mimba; Ni Ketut Rasmini (Universitas KH. Abdul Chalim Mojokerto, 2026)
The rapid growth of financial technology in Indonesia has encouraged the widespread use of Buy Now Pay Later (BNPL), particularly among Generation Z. While BNPL offers convenience and flexibility in digital transactions, its use also carries risks such as overspending, payment defaults, and long-term financial pressure. This study aims to analyze the influence of financial literacy, saving orientation, tendency for social comparison, and regulatory environment on the decision to use BNPL services among Generation Z in Bali, with perceived behavioral control serving as a mediating variable. This research adopts a quantitative associative approach. The population consists of Generation Z individuals domiciled in Bali who have used BNPL services, with a sample of 400 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using Partial Least Squares (PLS). The findings are expected to show that financial literacy and saving orientation tend to reduce BNPL usage decisions, while tendency for social comparison and regulatory environment tend to increase them. Perceived behavioral control is also expected to play an important mediating role in explaining how cognitive, behavioral, social, and external factors shape BNPL usage decisions. This study contributes to the literature on behavioral accounting and digital financial behavior, particularly in understanding the financial decision-making patterns of Generation Z in the context of short-term digital credit in Bali.